Method for promoting dispersion of spiral carbon nanofibers in rubber, application and rubber composite material
Through ionic liquid modification and centrifugal spray drying technology, one-dimensional nanocarbon filler/silver black composite powder was prepared, solving the problem of poor dispersion of spiral nanocarbon fibers in rubber matrix, and significantly improving the mechanical properties and wear resistance of rubber composite materials.
Patent Information
- Application Number
- CN202411874408.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The prior art is difficult to effectively disperse spiral nanocarbon fibers in rubber matrix, resulting in limited improvement in the mechanical properties of rubber composite materials.
By mixing ionic liquid, water and one-dimensional nanocarbon filler to modify, an ionic liquid modified one-dimensional nanocarbon filler slurry is obtained, and mixed with white carbon black for centrifugal spray-drying to prepare a one-dimensional nanocarbon filler/silver black composite powder to improve its dispersion in rubber.
The 300% fixed extension stress, tensile strength of the fracture, tear strength and wear resistance of the rubber composite material are significantly improved, while reducing the compression permanent deformation rate.
Smart Images

Figure CN119570082A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber, and in particular relates to a method for promoting the dispersion of spiral carbon nanofibers in rubber and an application thereof, and a rubber composite material. Background Art
[0002] Rubber composite materials are materials that are based on rubber and are combined with reinforcing materials, filling materials and / or modified materials. They have excellent mechanical, electrical and other comprehensive properties and are widely used in various fields.
[0003] Commonly used rubber reinforcement materials are one-dimensional nano carbon fillers, including spiral nano carbon fibers, linear carbon fibers, linear carbon nanotubes and spiral carbon nanotubes, etc., wherein the spiral nano carbon fibers are nano carbons with a special spiral structure, which not only have the excellent performance of traditional linear carbon nanotubes, but also have the advantages brought by the multi-dimensional spiral structure. In the rubber matrix, more rubber molecular chains can be wound and adsorbed by virtue of its special spiral morphological structure, thereby bringing better reinforcement effect. However, to achieve the performance advantages of spiral carbon nanotube reinforced rubber, it must be well dispersed in the rubber matrix as a prerequisite, but due to its special spiral structure, it is difficult to disperse in the rubber matrix, and the dispersibility of other one-dimensional nano carbon fillers in the rubber matrix also needs to be improved. In the prior art, in order to improve the dispersibility of spiral nano carbon fibers, it is combined with latex-like SBR, and a tearing agent is added to tear and pinch, and then a flocculant is added to coagulate and dry, but the flocculant used will remain in the rubber composite material, which is not conducive to the improvement of the mechanical properties of the rubber composite material. Therefore, how to improve the dispersibility of one-dimensional nanocarbon fillers such as spiral nanocarbon fibers in the rubber matrix, thereby improving the mechanical properties of rubber composites has become a difficult problem in the prior art. Summary of the invention
[0004] The purpose of the present invention is to provide a method and application for promoting the dispersion of spiral carbon nanofibers in rubber and a rubber composite material. The method provided by the present invention can promote better dispersion of one-dimensional nanocarbon fillers such as spiral carbon nanofibers in a rubber matrix, thereby improving the comprehensive performance of the rubber composite material.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for promoting dispersion of one-dimensional nano carbon filler in rubber, comprising the following steps:
[0007] (1) mixing an ionic liquid, water and a one-dimensional carbon nanofiller, and modifying the mixture to obtain an ionic liquid-modified one-dimensional carbon nanofiller slurry; the one-dimensional carbon nanofiller comprises at least one of a helical carbon nanofiber, a linear carbon fiber, a linear carbon nanotube and a helical carbon nanotube;
[0008] (2) mixing white carbon black and water to obtain white carbon black slurry;
[0009] (3) mixing the ionic liquid modified one-dimensional nano carbon filler slurry obtained in step (1) and the white carbon black slurry obtained in step (2), and performing centrifugal spray drying to obtain a one-dimensional nano carbon filler / white carbon black composite powder;
[0010] There is no order of precedence for steps (1) and (2).
[0011] Preferably, the ionic liquid in step (1) comprises at least one of imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids and quaternary phosphine ionic liquids.
[0012] Preferably, in step (1), the mass ratio of the ionic liquid to the one-dimensional nano-carbon filler is (0.25-2.5): (0.5-5).
[0013] Preferably, the modification time in step (1) is 1 to 3 hours.
[0014] Preferably, in the step (3), the mass ratio of the one-dimensional nano-carbon filler in the ionic liquid modified one-dimensional nano-carbon filler slurry to the white carbon in the white carbon slurry is (0.5-5): (45-49.5).
[0015] Preferably, in step (3), the temperature of the centrifugal spray drying is 100-400° C., the rotation speed of the centrifugal spray drying is 10000-24000 rpm, and the flow rate of the centrifugal spray drying is 10-100 mL / min.
[0016] The present invention also provides a one-dimensional nano carbon filler / white carbon black composite powder obtained by the method described in the above technical solution.
[0017] The present invention also provides the use of the one-dimensional nano carbon filler / white carbon black composite powder described in the above technical solution as a rubber reinforcing filler.
[0018] The present invention also provides a rubber composite material, which comprises the following components in parts by weight: 100 parts of natural rubber and / or EPDM rubber, 0.3 to 3 parts of softening plasticizer, 2 to 7 parts of vulcanization activator, 0.5 to 2.5 parts of antioxidant, 1.5 to 6.5 parts of accelerator, 1 to 3 parts of vulcanizer, 3 to 5 parts of activating dispersant and 40 to 80 parts of one-dimensional nano-carbon filler / white carbon black composite powder, wherein the one-dimensional nano-carbon filler / white carbon black composite powder is the one-dimensional nano-carbon filler / white carbon black composite powder described in the above technical scheme.
[0019] Preferably, the antioxidant includes at least one of antioxidant 4010NA, antioxidant 264, antioxidant 4020, antioxidant MB and antioxidant RD.
[0020] The present invention provides a method for promoting the dispersion of a one-dimensional nano-carbon filler in rubber, comprising the following steps: (1) mixing an ionic liquid, water and a one-dimensional nano-carbon filler, and performing modification to obtain an ionic liquid-modified one-dimensional nano-carbon filler slurry; the one-dimensional nano-carbon filler comprises at least one of spiral nano-carbon fibers, linear carbon fibers, linear carbon nanotubes and spiral carbon nanotubes; (2) mixing white carbon black and water to obtain white carbon black slurry; (3) mixing the ionic liquid-modified one-dimensional nano-carbon filler slurry obtained in step (1) and the white carbon black slurry obtained in step (2), and performing centrifugal spray drying to obtain a one-dimensional nano-carbon filler / white carbon black composite powder; steps (1) and (2) are performed in no particular order. The present invention utilizes the extremely strong wettability of ionic liquid to modify one-dimensional nanocarbon fillers such as spiral nanocarbon fibers to enhance their hydrophilicity; adding white carbon black reduces the interaction between one-dimensional nanocarbon fillers such as spiral nanocarbon fibers, promotes the firm interface bonding between one-dimensional nanocarbon filler / white carbon black composite powder and rubber, and can have good dispersibility after being added to the rubber matrix, thereby improving the comprehensive performance of the rubber composite material. The results of the embodiment show that the spiral nanocarbon fiber / white carbon black composite powder prepared by the present invention is used in a rubber composite material, and compared with the spiral nanocarbon fiber not modified by ionic liquid and the rubber composite material without adding spiral nanocarbon fiber, the 300% tensile stress, tensile strength at break, tear strength and wear resistance of the rubber composite material can be improved, and the compression permanent deformation rate can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the SEM image of the spiral carbon nanofiber in Example 1;
[0022] Figure 2 This is the SEM image of the 1-butyl-3-methylimidazole tetrafluoroborate modified helical nanocarbon fiber / white carbon black composite powder in Example 1. DETAILED DESCRIPTION
[0023] The present invention provides a method for promoting dispersion of one-dimensional nano carbon filler in rubber, comprising the following steps:
[0024] (1) mixing an ionic liquid, water and a one-dimensional nano-carbon filler, and modifying the mixture to obtain an ionic liquid-modified one-dimensional nano-carbon filler slurry;
[0025] (2) mixing white carbon black and water to obtain white carbon black slurry;
[0026] (3) mixing the ionic liquid modified one-dimensional nano carbon filler slurry obtained in step (1) and the white carbon black slurry obtained in step (2), and performing centrifugal spray drying to obtain a one-dimensional nano carbon filler / white carbon black composite powder;
[0027] There is no order of precedence for steps (1) and (2)
[0028] The invention mixes ionic liquid, water and one-dimensional nano carbon filler, performs modification, and obtains ionic liquid modified one-dimensional nano carbon filler slurry.
[0029] In the present invention, the ionic liquid preferably includes at least one of imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids and quaternary phosphine ionic liquids, more preferably at least one of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylpyridine tetrafluoroborate, triethylmethylammonium tetrafluoroborate and tricyclohexylphosphine tetrafluoroborate, and most preferably 1-butyl-3-methylimidazolium tetrafluoroborate. The present invention utilizes the extremely strong wettability of ionic liquids to modify one-dimensional nano-carbon fillers such as spiral nano-carbon fibers, enhance their hydrophilicity, improve the dispersibility of one-dimensional nano-carbon filler / white carbon black composite powder in the rubber matrix, and improve the comprehensive performance of rubber composite materials. The present invention selects the above-mentioned ionic liquid, which can further improve the dispersibility of one-dimensional nano-carbon filler / white carbon black composite powder in the rubber matrix.
[0030] In the present invention, the one-dimensional nano-carbon filler includes at least one of spiral nano-carbon fibers, linear carbon fibers, linear carbon nanotubes and spiral carbon nanotubes.
[0031] The present invention has no special limitation on the size of the one-dimensional nanocarbon filler, which can be selected according to actual needs. In an embodiment of the present invention, the diameter of the spiral nanocarbon fiber is 30 to 100 nm; the thread pitch of the spiral nanocarbon fiber is 50 to 140 nm; and the length of the spiral nanocarbon fiber is 1 to 50 μm. The present invention has no special limitation on the source of the spiral nanocarbon fiber, and commercial products known to those skilled in the art can be used.
[0032] In the present invention, the mass ratio of the ionic liquid to the one-dimensional nano-carbon filler is preferably (0.25-2.5): (0.5-5), more preferably (0.5-2): (0.5-5), and further preferably (1-1.5): (0.5-5). The present invention controls the mass ratio of the ionic liquid to the one-dimensional nano-carbon filler within the above range. If the ionic liquid content is too low, the one-dimensional nano-carbon filler cannot be fully infiltrated, resulting in uneven dispersion. If the ionic liquid content is too high, the cross-linking density of the rubber will be reduced, resulting in a decrease in the mechanical properties of the rubber. In the present invention, the ionic liquid itself has the advantages of extremely low vapor pressure, non-volatile, good thermal stability, and environmental friendliness, and only a trace amount of addition is required to achieve effective modification of the one-dimensional nano-carbon filler.
[0033] The present invention has no particular limitation on the amount of water used, as long as the amount of water can fully mix and disperse the ionic liquid and the one-dimensional nano-carbon filler.
[0034] In the present invention, the mixing of the ionic liquid, water and one-dimensional nano-carbon filler is preferably: mixing the ionic liquid and water, and then adding the one-dimensional nano-carbon filler.
[0035] In the present invention, the mixing of the ionic liquid and water is preferably carried out under stirring conditions; the mixing rate of the ionic liquid and water is preferably 400 to 1600 rpm; and the mixing time of the ionic liquid and water is preferably 2 to 24 hours.
[0036] In the present invention, the modification is preferably carried out under ultrasonic conditions; the modification time is preferably 1 to 3 hours. In an embodiment of the present invention, the modification time may be specifically 1 hour, 2 hours or 3 hours. The present invention does not specifically limit the power of the ultrasound, and the ultrasound power well known to those skilled in the art can be used. The present invention controls the modification method and time within the above range, which can make the modification more sufficient.
[0037] The invention mixes white carbon black and water to obtain white carbon black slurry.
[0038] The present invention has no special limitation on the particle size of the white carbon black, which can be selected according to actual needs. In an embodiment of the present invention, the primary structure particle size of the white carbon black is 7 to 120 nm; the secondary structure particle size of the white carbon black is 0.5 to 50 μm.
[0039] The present invention has no particular limitation on the amount of water used, as long as it can fully disperse the white carbon black.
[0040] In the present invention, the mixing of white carbon black and water is preferably carried out under stirring conditions; the stirring rate is preferably 400 to 1600 rpm; and the stirring time is preferably 2 to 24 hours.
[0041] After obtaining the ionic liquid modified one-dimensional nano carbon filler slurry and the white carbon black slurry, the present invention mixes the ionic liquid modified one-dimensional nano carbon filler slurry and the white carbon black slurry, and performs centrifugal spray drying to obtain the one-dimensional nano carbon filler / white carbon black composite powder.
[0042] In the present invention, the mass ratio of the one-dimensional nano-carbon filler in the ionic liquid modified one-dimensional nano-carbon filler slurry and the white carbon black in the white carbon black slurry is preferably (0.5-5): (45-49.5). In the present invention, the white carbon black reduces the interaction between the one-dimensional nano-carbon fillers such as the spiral nano-carbon fibers, promotes the firm interface bonding between the one-dimensional nano-carbon filler / white carbon black composite powder and the rubber, and improves the comprehensive performance of the rubber composite material. The present invention controls the mass ratio of the one-dimensional nano-carbon filler and the white carbon black within the above range, which can further improve the dispersibility of the one-dimensional nano-carbon filler / white carbon black composite powder in the rubber matrix.
[0043] In the present invention, the mixing of the ionic liquid modified one-dimensional nano carbon filler slurry and the white carbon black slurry is preferably carried out under stirring conditions; the stirring rate is preferably 400 to 1600 rpm; and the stirring time is preferably 2 to 24 hours.
[0044] In the present invention, the temperature of the centrifugal spray drying is preferably 100-400° C. In an embodiment of the present invention, the temperature of the centrifugal spray drying may be specifically 100° C., 150° C., 200° C., 250° C., 300° C., 350° C. or 400° C. In the present invention, if the temperature of the centrifugal spray drying is too low, the water content of the composite powder will be too high and cannot be used directly, while if the temperature of the centrifugal spray drying is too high, the composite powder will lose its surface activity and the ionic liquid will decompose.
[0045] In the present invention, the rotation speed of the centrifugal spray drying is preferably 10000-24000rpm. In an embodiment of the present invention, the rotation speed of the centrifugal spray drying can specifically be 10000rpm, 11000rpm, 12000rpm, 13000rpm, 14000rpm, 15000rpm, 16000rpm, 17000rpm, 18000rpm, 19000rpm, 20000rpm, 21000rpm, 22000rpm, 23000rpm or 24000rpm.
[0046] In the present invention, the flow rate of the centrifugal spray drying is preferably 10 to 100 mL / min. In an embodiment of the present invention, the flow rate of the centrifugal spray drying can be specifically 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, 90 mL / min or 100 mL / min. In the present invention, if the speed of the centrifugal spray drying is too low and the flow rate is too high, the particle size of the composite powder will be too large, affecting the rubber performance, while if the speed is too high and the flow rate is too low, the yield of the composite powder will be too low and energy will be wasted.
[0047] The present invention uses centrifugal spray drying to quickly dry the one-dimensional nano carbon filler / white carbon black slurry, obtain uniform and fine composite powder, and avoid sedimentation, stratification and agglomeration. The present invention has no special limitation on the centrifugal spray drying equipment, and a spray drying equipment well known to those skilled in the art can be used. In an embodiment of the present invention, the centrifugal spray drying equipment can be an LPG-5 centrifugal spray dryer.
[0048] The method of the present invention has a simple process flow, is suitable for large-scale production and application, can give full play to the super strong reinforcement effect of one-dimensional nano-carbon fillers such as spiral nano-carbon fibers, and achieves that the comprehensive mechanical properties of natural rubber / ethylene propylene diene monomer rubber composite materials can be significantly improved by adding a trace amount of one-dimensional nano-carbon fillers such as spiral nano-carbon fibers.
[0049] The present invention also provides a one-dimensional nano carbon filler / white carbon black composite powder obtained by the method described in the above technical solution.
[0050] In the present invention, the one-dimensional nano-carbon filler in the one-dimensional nano-carbon filler / white carbon black composite powder is uniformly embedded between the white carbon black particles.
[0051] In the present invention, the particle size of the one-dimensional nano carbon filler / white carbon black composite powder is preferably 1 to 55 μm. The present invention controls the particle size of the one-dimensional nano carbon filler / white carbon black composite powder within the above range, which can further improve the comprehensive performance of the rubber composite material.
[0052] The present invention also provides the use of the one-dimensional nano carbon filler / white carbon black composite powder described in the above technical solution as a rubber reinforcing filler.
[0053] The present invention has no particular limitation on the type of rubber, and any type of rubber well known to those skilled in the art can be used.
[0054] The present invention has no special limitation on the operation of the application, and the technical solutions of the application well known to those skilled in the art may be adopted.
[0055] The present invention also provides a rubber composite material, which comprises the following components in parts by weight: 100 parts of natural rubber and / or EPDM rubber, 0.3 to 3 parts of softening plasticizer, 2 to 7 parts of vulcanization activator, 0.5 to 2.5 parts of antioxidant, 1.5 to 6.5 parts of accelerator, 1 to 3 parts of vulcanizer, 3 to 5 parts of activating dispersant and 40 to 80 parts of one-dimensional nano-carbon filler / white carbon black composite powder, wherein the one-dimensional nano-carbon filler / white carbon black composite powder is the one-dimensional nano-carbon filler / white carbon black composite powder of the above technical solution.
[0056] Unless otherwise specified, the present invention has no particular limitation on the sources of the components, and commercially available products known to those skilled in the art may be used.
[0057] The rubber composite material provided by the present invention includes 100 parts by weight of natural rubber and / or EPDM rubber. When the rubber composite material includes natural rubber and EPDM rubber, the present invention has no particular limitation on the ratio of the natural rubber and EPDM rubber, and any ratio can be used.
[0058] The rubber composite material provided by the present invention comprises 0.3 to 3 parts of a softening plasticizer based on 100 parts of natural rubber and / or EPDM rubber. In an embodiment of the present invention, the amount of the softening plasticizer may be specifically 0.3 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts or 3 parts.
[0059] In the present invention, the softening plasticizer is preferably stearic acid.
[0060] The rubber composite material provided by the present invention comprises 2 to 7 parts of a vulcanizing agent based on 100 parts of natural rubber and / or EPDM rubber. In an embodiment of the present invention, the amount of the vulcanizing agent used may be specifically 2 parts, 3 parts, 4 parts, 5 parts, 6 parts or 7 parts.
[0061] In the present invention, the vulcanization activator is preferably zinc oxide. The present invention has no particular limitation on the particle size of the zinc oxide, and a commercial product well known to those skilled in the art can be used.
[0062] The rubber composite material provided by the present invention comprises 0.5 to 2.5 parts of an antioxidant based on 100 parts of natural rubber and / or EPDM rubber. In an embodiment of the present invention, the amount of the antioxidant may be specifically 0.5 parts, 1 parts, 1.5 parts, 2 parts or 2.5 parts.
[0063] In the present invention, the antioxidant preferably includes at least one of antioxidant 4010NA, antioxidant 264, antioxidant 4020, antioxidant MB and antioxidant RD.
[0064] The rubber composite material provided by the present invention comprises 1.5 to 6.5 parts of accelerator based on 100 parts of natural rubber and / or EPDM rubber. In an embodiment of the present invention, the amount of the accelerator can be specifically 1.5 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts or 6.5 parts.
[0065] In the present invention, the promoter preferably includes at least one of promoter CZ, promoter NS, promoter AZ, promoter BSO, promoter ARZ, promoter DIBS, promoter TMTD, promoter TMTM, promoter PMTM, promoter TETD, promoter PTD and promoter TMTT, and more preferably includes promoter CZ and promoter TMTD.
[0066] In the present invention, when the accelerator includes accelerator CZ and accelerator TMTD, the mass ratio of accelerator CZ to accelerator TMTD is preferably (1-3):1, more preferably 2:1.
[0067] The rubber composite material provided by the present invention comprises 1 to 3 parts of a vulcanizing agent based on 100 parts of natural rubber and / or EPDM rubber. In an embodiment of the present invention, the amount of the vulcanizing agent used may be specifically 1 part, 2 parts or 3 parts.
[0068] In the present invention, the vulcanizing agent is preferably sulfur.
[0069] The rubber composite material provided by the present invention comprises 3 to 5 parts of an activated dispersant based on 100 parts of natural rubber and / or EPDM rubber. In an embodiment of the present invention, the amount of the activated dispersant may be specifically 3 parts, 4 parts or 5 parts.
[0070] In the present invention, the activated dispersant is preferably polyethylene glycol, more preferably polyethylene glycol 4000.
[0071] Taking the mass of natural rubber and / or EPDM rubber as 100 parts, the rubber composite material provided by the present invention includes 40 to 80 parts of one-dimensional nano-carbon filler / white carbon black composite powder. In an embodiment of the present invention, the amount of the one-dimensional nano-carbon filler / white carbon black composite powder can be specifically 40 parts, 50 parts, 60 parts, 70 parts or 80 parts.
[0072] The present invention controls the composition of the rubber composite material and the amount of each component, and further improves the comprehensive performance of the rubber composite material.
[0073] The present invention has no particular limitation on the method for preparing the rubber composite material, and any method for preparing the rubber composite material well known to those skilled in the art may be used.
[0074] In the present invention, when natural rubber and EPDM rubber are included, the preparation method of the rubber composite material is preferably: the natural rubber is plasticized and then rolled, and then the EPDM rubber is added for rolling, and then a softening plasticizer, a vulcanization activator, an antioxidant, a accelerator and an activated dispersant are added for the first mixing, and finally a one-dimensional nano-carbon filler / white carbon black composite powder and a vulcanizer are added, and the second mixing, thin passing, triangle packing, sheeting and vulcanization are carried out in sequence to obtain the rubber composite material.
[0075] In the present invention, the temperature of the mastication is preferably 20-40° C., more preferably 30° C.; the time of the mastication is preferably 5-15 min, more preferably 10 min.
[0076] In the present invention, the temperature of the first mixing is preferably 20-30° C., more preferably 25° C.; the time of the first mixing is preferably 1-10 min, more preferably 5 min.
[0077] In the present invention, the temperature of the second kneading is preferably 50-60° C., more preferably 55° C.; the time of the second kneading is preferably 1-10 min, more preferably 5 min.
[0078] In the present invention, the number of thin passes is preferably 5 to 7 times, more preferably 6 times.
[0079] In the present invention, the number of times of making triangle packs is preferably 5 to 7 times, more preferably 6 times.
[0080] In the present invention, the vulcanization temperature is preferably 150-180° C., more preferably 160-170° C.; the vulcanization time is preferably 1-10 min, more preferably 5 min.
[0081] The present invention controls various parameters in the preparation method within the above range, which can further improve the comprehensive performance of the rubber composite material.
[0082] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0083] Example 1
[0084] A method for promoting the dispersion of helical nanocarbon fibers in rubber: (1) using a high-speed stirrer to stir 1 g of ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate and water at 800 rpm for 2 h, adding 2 g of helical nanocarbon fibers (with a diameter of 30 to 100 nm, a thread pitch of 50 to 140 nm, a length of 1 to 50 μm, and a mass ratio of ionic liquid to helical nanocarbon fibers of 0.5:1), and ultrasonically oscillating for 2 h to obtain an ionic liquid-modified helical nanocarbon fiber slurry;
[0085] (2) 48 g of white carbon black (primary structure particle size of 7 to 120 nm, secondary structure particle size of 0.5 to 50 μm) and water were mixed, and stirred at 1000 rpm for 2 h using a high-speed stirrer to obtain a white carbon black slurry;
[0086] (3) adding the ionic liquid modified helical nanocarbon fiber slurry obtained in step (1) to the white carbon black slurry in step (2) while stirring at a speed of 1000 rpm (the mass ratio of the helical nanocarbon fiber to the white carbon black is 2:48), and continuing stirring for 6 hours to obtain a helical nanocarbon fiber / white carbon black mixed slurry;
[0087] (4) The spiral nanocarbon fiber / white carbon black mixed slurry obtained in step (3) is subjected to high-speed centrifugal spray drying at 50 mL / min, 245°C, and 16000 rpm to obtain 1-butyl-3-methylimidazole tetrafluoroborate modified spiral nanocarbon fiber / white carbon black composite powder (particle size 1 to 55 μm).
[0088] Example 2
[0089] The ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate in Example 1 was replaced by 1-butyl-3-methylpyridinium tetrafluoroborate, and the other parameters were the same as those in Example 1.
[0090] Example 3
[0091] The ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate in Example 1 was replaced by triethylmethylammonium tetrafluoroborate, and the other parameters were the same as those in Example 1.
[0092] Example 4
[0093] The ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate in Example 1 was replaced by tricyclohexylphosphine tetrafluoroborate, and the other parameters were the same as those in Example 1.
[0094] Comparative Example 1
[0095] The ionic liquid in Example 1 was omitted to obtain an unmodified helical carbon nanofiber / white carbon black composite powder.
[0096] Comparative Example 2
[0097] White carbon black.
[0098] The spiral nanocarbon fibers in Example 1 were observed using a scanning electron microscope, and the SEM images obtained were as follows: Figure 1 As shown; the 1-butyl-3-methylimidazolium tetrafluoroborate modified helical nanocarbon fiber / white carbon black composite powder in Example 1 was observed using a scanning electron microscope, and the obtained SEM image was as shown Figure 2 As shown. Figure 1 and Figure 2 It can be seen that for the spiral nanocarbon fibers that have not been modified with ionic liquids, a large number of fibers are tightly entangled with each other and aggregated into clusters. However, after being modified with ionic liquids, the spiral nanocarbon fibers are untangled and are evenly embedded in the white carbon black in the form of single fibers.
[0099] Application Example 1
[0100] A rubber composite material: composed of the following components by weight: 60 parts of natural rubber, 40 parts of EPDM rubber, 1 part of stearic acid, 5 parts of zinc oxide, 1.5 parts of antioxidant 4010NA, 3 parts of accelerator CZ, 1.5 parts of accelerator TMTD, 40004 parts of polyethylene glycol, 51 parts of 1-butyl-3-methylimidazole tetrafluoroborate modified helical nanocarbon fiber / white carbon black composite powder in Example 1, and 2 parts of sulfur;
[0101] The preparation method of the rubber composite material is as follows: natural rubber is plasticized on a double-roll mill (the plasticizing temperature is 30° C. and the time is 10 minutes), then rolled, EPDM rubber is added for rolling, then stearic acid, zinc oxide, antioxidant 4010NA, accelerator CZ, accelerator TMTD and polyethylene glycol 4000 are added in sequence, 1-butyl-3-methylimidazole tetrafluoroborate modified spiral nanocarbon fiber / white carbon black composite powder is added after mixing at 25° C. for 5 minutes, sulfur is added, mixing at 55° C. for 5 minutes, thinning 6 times, triangle packing 6 times, finally discharging, and vulcanizing at 160° C. for 5 minutes to obtain the rubber composite material.
[0102] Application Example 2
[0103] The 1-butyl-3-methylimidazole tetrafluoroborate modified helical nano-carbon fiber / white carbon black composite powder in Application Example 1 is replaced by the helical nano-carbon fiber / white carbon black composite powder in Example 2, and the other parameters are the same as those in Application Example 1.
[0104] Application Example 3
[0105] The 1-butyl-3-methylimidazole tetrafluoroborate modified helical nano-carbon fiber / white carbon black composite powder in Application Example 1 is replaced by the helical nano-carbon fiber / white carbon black composite powder in Example 3, and the other parameters are the same as those in Application Example 1.
[0106] Application Example 4
[0107] The 1-butyl-3-methylimidazole tetrafluoroborate modified helical nano-carbon fiber / white carbon black composite powder in Application Example 1 is replaced by the helical nano-carbon fiber / white carbon black composite powder in Example 4, and the other parameters are the same as those in Application Example 1.
[0108] Comparative application example 1
[0109] The 1-butyl-3-methylimidazole tetrafluoroborate modified helical nanocarbon fiber / white carbon black composite powder in Application Example 1 was replaced with the unmodified helical nanocarbon fiber / white carbon black composite powder in Comparative Example 1, and the other parameters were the same as those in Application Example 1.
[0110] Comparative Application Example 2
[0111] The 1-butyl-3-methylimidazole tetrafluoroborate modified helical nanocarbon fiber / white carbon black composite powder in Application Example 1 was replaced with the white carbon black in Comparative Example 2, and the other parameters were the same as those in Application Example 1.
[0112] The 300% elongation stress, tensile strength at break, tear strength, compression permanent deformation rate and relative volume wear of the rubber composite materials in application examples 1 to 4 and comparative application examples 1 to 2 were tested, wherein the 300% elongation stress and tensile strength at break were determined by GB / T528-2009, the tear strength was determined by a right-angle specimen of GB / T 529-2008, the compression permanent deformation rate after compression for 24 hours at 25°C was determined by GB / T 7759.1-2015, and the wear resistance (relative volume wear) was determined by GB / T 9867-2008. The results are shown in Table 1.
[0113] Table 1 300% elongation stress, tensile strength at break, tear strength, compression set and relative volume wear of the rubber composite materials in Application Examples 1 to 4 and Comparative Application Examples 1 to 2
[0114]
[0115] As can be seen from Table 1, the spiral nanocarbon fiber / white carbon black composite powder modified by ionic liquid is used to reinforce the natural rubber / EPDM rubber system. Compared with the spiral nanocarbon fiber not modified by ionic liquid and the rubber sample without adding spiral nanocarbon fiber, its 300% tensile stress, tensile strength at break and tear strength are all improved to varying degrees, and the compression permanent deformation rate is reduced. Among them, the spiral nanocarbon fiber / white carbon black composite powder modified by 1-butyl-3-methylimidazole tetrafluoroborate has the most significant effect, which can effectively overcome the problem of easy agglomeration of spiral nanocarbon fibers in rubber, thereby further improving the comprehensive performance of rubber composite materials.
[0116] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for promoting the dispersion of one-dimensional nanocarbon fillers in rubber, comprising the following steps: (1) mixing an ionic liquid, water and a one-dimensional carbon nanofiller, and modifying the mixture to obtain an ionic liquid-modified one-dimensional carbon nanofiller slurry; the one-dimensional carbon nanofiller comprises at least one of a helical carbon nanofiber, a linear carbon fiber, a linear carbon nanotube and a helical carbon nanotube; (2) mixing white carbon black and water to obtain white carbon black slurry; (3) mixing the ionic liquid modified one-dimensional nano carbon filler slurry obtained in step (1) and the white carbon black slurry obtained in step (2), and performing centrifugal spray drying to obtain a one-dimensional nano carbon filler / white carbon black composite powder; There is no order of precedence for steps (1) and (2).
2. The method according to claim 1, characterized in that: The ionic liquid in step (1) includes at least one of imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids and quaternary phosphine ionic liquids.
3. The method according to claim 1, characterized in that In the step (1), the mass ratio of the ionic liquid to the one-dimensional nano carbon filler is (0.25-2.5): (0.5-5).
4. The method according to claim 1, characterized in that: The modification time in step (1) is 1 to 3 hours.
5. The method according to claim 1, characterized in that In the step (3), the mass ratio of the one-dimensional nano-carbon filler in the ionic liquid modified one-dimensional nano-carbon filler slurry to the white carbon black in the white carbon black slurry is (0.5-5): (45-49.5).
6. The method according to claim 1, characterized in that In the step (3), the temperature of the centrifugal spray drying is 100-400° C., the rotation speed of the centrifugal spray drying is 10000-24000 rpm, and the flow rate of the centrifugal spray drying is 10-100 mL / min.
7. The one-dimensional nano carbon filler / white carbon black composite powder obtained by the method according to any one of claims 1 to 6.
8. Use of the one-dimensional nano carbon filler / white carbon black composite powder as claimed in claim 7 as a rubber reinforcing filler.
9. A rubber composite material, comprising the following components in parts by weight: 100 parts of natural rubber and / or EPDM rubber, 0.3-3 parts of softening plasticizer, 2-7 parts of vulcanization activator, 0.5-2.5 parts of antioxidant, 1.5-6.5 parts of accelerator, 1-3 parts of vulcanizer, 3-5 parts of activating dispersant and 40-80 parts of one-dimensional nano-carbon filler / white carbon black composite powder, wherein the one-dimensional nano-carbon filler / white carbon black composite powder is the one-dimensional nano-carbon filler / white carbon black composite powder as described in claim 7.
10. The rubber composite material according to claim 9, characterized in that: The antioxidant includes at least one of antioxidant 4010NA, antioxidant 264, antioxidant 4020, antioxidant MB and antioxidant RD.
Citation Information
Patent Citations
Neoprene / carboxylated multiwalled carbon nanotube composite material modified by carboxylated imidazole ionic liquid and preparing method
CN105175837A
Spiral nano carbon fiber reinforced rubber composite material and preparation method thereof
CN113861459A
Preparation method of modified graphene / white carbon black composite filler, composite filler, rubber composite material and preparation method of modified graphene / white carbon black composite filler
CN115197471A
Method for preparing high performance tread rubber by filler silylation reaction catalyzed in-situ by ionic liquid
WO2016169484A1